The semi-naked inspection. Opinions of and on the education inspection - Santamaría Luna, Rogeli (Avances en Supervisión Educativa, 2013)
This article analyzes the status quo of the Inspectorate of Education, through a program based on the different opinions about the Valencian Inspectorate. It is focused on the area of Castellón, but it could perfectly be extended to the rest of Spain.It is not an empirical neither bibliographical research. It is not a cases study but it is just a serie of opinions. It should be noted the paucity of empirical research on this issue in Spain.It can be useful in order to think about the situation of the inspectorate in Valencian Community, and after this research the inspectorate can see the needs of the educational system in our changing society.After defining the objectives, the autor describes the context of the Valencian Community inspectorate from his personal vision and he exposes the method of work.In order to get the objectives, he carries out some interviews to members who have been working in the Valencian Inspectorate during 2012. The question that has been asked is their opinion about the professional skills of the inspectorate of education, and their own professional satisfaction. These data are compared to the results obtained from the teachers’ interviews about the same topic.Finally it has gathered some opinions from newspapers and articles, in order to reach the final conclusions.
Keywords: reviews; inspection of education; Valencia